A Bibliometric Review of the Knowledge Base on Capital Structure Decisions. Issue 2 (April 2023) - Priyan, P. K.; Nyabakora, Wakara Ibrahimu; Rwezimula, Geofrey
The purpose of this study is to review the knowledge base on capital structure decisions. The Scopus database was used for the bibliometric review of the area in question. The sampling process was performed employing the PRISMA approach. The VOSviewer software was used to analyse 2, 979 articles. This identified the network growth, the most contributors, the context of the intellectual structure, the most studied topic and the research gap for future studies. We have found that the year 1989 marked the abolition of research on capital structure for articles in the Scopus database. As the period was divided into three sub-periods, the terms 'capital structure' and 'leverage' appeared throughout. Also, the recent themes as depicted in the density map are corporate governance, dividend policy, testing the trade-off theory against pecking order theories, speed of adjustments and corporate social responsibility. However, there are research gaps found due to the newness of the terms and the frequency of terms' persistence in the current sub-period. The findings will provide researchers with knowledge about the past, current and future implications as well as the gaps for their studies.